The Rate of Litter Production in Mangrove Forest at Siar Beach, Lundu, Sarawak - Othman, Saberi (1989)
A study of litter production was conducted at Siar Beach, mangrove forest, near Lundu, Sarawak. There are nine species of trees in this forest of which Rhizome mucronata is the dominant and R. apiculata is the co-dominant species. The rate of litter production was 5.72 t/ha/year, and of this 4.49 t/ha/year (78.5 %) was leaf litter. The production of litter fluctuates being higher during April to June and December to February compared to other months.